Seismic performance of reinforced concrete bridge using friction pendulum bearing under different friction coefficients - James Michael; Muslinang Moestopo; Iswandi Imran; Dionysius M. Siringoringo; Erwin Lim; Shinsuke Yamazaki (Universitas Islam Sultan Agung, 2022)
Application of seismic isolation system is important in bridges design, primarily in seismically active countries. Bridges are prone to damage from seismic forces. Elastomeric isolation bearings have been applied in short-span bridges for some time in most countries. These bearings are preferred because of the low maintenance cost. However, these bearings are not reliable when subjected to large displacement and low temperatures. In the other hand, friction sliding bearings shows better performance under the former circumstances despite its use is still limited to long-span bridges and has not been explored further. This paper describes a performance evaluation of seismically-isolated short-span reinforced concrete bridge using friction pendulum system (FPS). Seismic performances of non-isolated and isolated models from the reference bridge functioning as light rapid transit (LRT) bridge in Jakarta are investigated using nonlinear time history analysis. The results demonstrate that isolated bridges with FPS performed better than non-isolated bridges under 1000-year earthquake as shown by reductions of base shear force, absolute deck acceleration, and acceleration amplification ratio. Comparisons of isolated bridges with different FPS friction types and arrangement have demonstrated that the reference bridge with all Type A friction (µ0 = 0.050) applied, performed the best among all other configurations.